2001
DOI: 10.1016/s0092-8674(01)00573-6
|View full text |Cite
|
Sign up to set email alerts
|

The VERNALIZATION 2 Gene Mediates the Epigenetic Regulation of Vernalization in Arabidopsis

Abstract: The acceleration of flowering by a long period of low temperature, vernalization, is an adaptation that ensures plants overwinter before flowering. Vernalization induces a developmental state that is mitotically stable, suggesting that it may have an epigenetic basis. The VERNALIZATION2 (VRN2) gene mediates vernalization and encodes a nuclear-localized zinc finger protein with similarity to Polycomb group (PcG) proteins of plants and animals. In wild-type Arabidopsis, vernalization results in the stable reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
423
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 534 publications
(442 citation statements)
references
References 56 publications
15
423
2
2
Order By: Relevance
“…Vernalization down regulates the expression of FLC and maintaining this repression requires epigenetic regulation mediated by VERNALIZATION 2 (Accession number AF284500), a gene with similarity to the polycomb group of proteins [42]. The levels of FLC are crucial for the vernalization response and the interaction between FCA (Accession number Z82992) and FY (Accession number NM_121351) appears to regulate FLC mRNA 3 0 end formation providing a fine-tuning mechanism [43].…”
Section: Environmental Signals Antagonize Negative Regulatorsmentioning
confidence: 99%
“…Vernalization down regulates the expression of FLC and maintaining this repression requires epigenetic regulation mediated by VERNALIZATION 2 (Accession number AF284500), a gene with similarity to the polycomb group of proteins [42]. The levels of FLC are crucial for the vernalization response and the interaction between FCA (Accession number Z82992) and FY (Accession number NM_121351) appears to regulate FLC mRNA 3 0 end formation providing a fine-tuning mechanism [43].…”
Section: Environmental Signals Antagonize Negative Regulatorsmentioning
confidence: 99%
“…Because FLC is a flowering repressor, the gene which is upregulated by DNA demethylation is not FLC itself. The gene(s) upstream of FLC, such as VERNALIZATION1 (VRN1), VERNALIZATION2 (VRN2) or VERNALIZATION INSENSITIVE3 (VIN3) (Gendall et al 2001, Levy et al 2002, Sung and Amasino 2004, may be upregulated by DNA demethylation.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the flowering repressor gene FLC is significant up-regulated in sdr6 ( Figure 5). However, expression levels of key components CO and GI in the photoperiod pathway; SPY in the GA pathway (Tseng et al 2004); and VRN2 in the vernalization pathway (Gendall et al 2001;Levy et al 2002) were not significantly different from the wild-type and sdr6/SDR6 plants. These results suggested that the autonomous pathway is compromised in sdr6 plants, which led to later flowering when compared with the wild-type.…”
Section: Sdr6 Deficiency Altered the Expression Of Critical Genes In mentioning
confidence: 74%